2009
DOI: 10.4314/tjs.v31i1.18412
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of mercury content in human hair and cosmetic products used in Dar es Salaam, Tanzania

Abstract: Total mercury (T-Hg) concentrations were analysed in human hairs and cosmetic products sold in Dar es Salaam Tanzania. The average total mercury (T-Hg) concentrations in the scalp hair of females using mercury based cosmetic creams and soaps ranged from 7.0 ± 0.4 to 880 ± 12 ppm.Highest T-Hg concentrations were found in females who work in beauty hair salons and the lowest concentrations were found among students. The average values in non-cosmetic users were found to be lower, with mercury ranging from 0.57 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 3 publications
2
13
0
1
Order By: Relevance
“…However, previous studies conducted by Al-Saleh and Al-Doush ( 1997 ) on mercury concentration in creams obtained from the Saudi Arabians market which originated from Asia and Middle East contained T-mercury concentration above the US FDA limit. Results of T-mercury determined in cosmetic products obtained on Dares Salaam market in Tanzania also showed very high concentration of mercury in some creams and soaps above the US FDA limit with T-mercury ranged from 0.11 to 8665 μg/g in cosmetic soaps and 0.16–25.30 μg/g in cosmetic creams (Kinabo 2003 ).…”
Section: Resultsmentioning
confidence: 98%
“…However, previous studies conducted by Al-Saleh and Al-Doush ( 1997 ) on mercury concentration in creams obtained from the Saudi Arabians market which originated from Asia and Middle East contained T-mercury concentration above the US FDA limit. Results of T-mercury determined in cosmetic products obtained on Dares Salaam market in Tanzania also showed very high concentration of mercury in some creams and soaps above the US FDA limit with T-mercury ranged from 0.11 to 8665 μg/g in cosmetic soaps and 0.16–25.30 μg/g in cosmetic creams (Kinabo 2003 ).…”
Section: Resultsmentioning
confidence: 98%
“…Nephro-toxic effects have been attributed to application of inorganic mercury salts. Exposure of mercury to placental cells causes damage to the developing foetus [25,27]. In other studies [28,29], observed that complications of mercurial toxicity include exogenous ochronosis, dermatitis, facial acnes, facial hypertricosis, hyper and hypo-pigmentation, reduction in the skin resistance to bacterial and fungal infections, anxiety, depression, psychosis, impaired wound healing, the fish odour syndrome, nephropaty, steroid addition syndrome and predisposition to infections.…”
Section: Resultsmentioning
confidence: 99%
“…A high concentration of mercury in pregnant women is known to considerably increase the risk of permanent brain damage and may lead to acrodymia (pink baby syndrome). Exposure of mercury to placental cells causes damage to the developing fetus [25,27]. Chronic exposure to either inorganic or organic mercury may damage brain, kidneys, nervous system and developing foetus [26].…”
Section: Resultsmentioning
confidence: 99%
“…UN reported that blood mercury level is 400 times greater in mercurial cosmetic users than nonusers [32]. According to WHO, mercury is a common ingredient found in skin lightening soaps and creams.…”
Section: Assessment Of Gender Difference Effect On Hhg Concentrationmentioning
confidence: 99%
“…Reference [32] compared total mercury in hairs of students with women associated with different occupations …”
Section: Assessment Of Working Status Effect On Hhg Concentrationmentioning
confidence: 99%